β-Glucan: Mode of Action and Its Uses in Fish Immunomodulation - Hadiuzzaman, Md; Moniruzzaman, Mohammad; Shahjahan, Md; Bai, Sungchul C.; Min, Taesun; Hossain, Zakir (Frontiers in Marine Science, 2022)
β-glucan is considered as an effective immunostimulant because of its binding capacity to different receptors on leukocytes leading to the stimulation of immune responses including bactericidal activity, cytokine productivity, and survival fit ability at cellular levels. In response to immune cell surface receptors, β-glucan stimulates to release cytokines and chemokines. It has been found that these signaling proteins eventually stimulate the immunocompetent cells in fish such as monocytes, macrophages, and neutrophils for killing pathogens by phagocytosis, oxidative burst, and cytotoxic killing activities. They also procreate immunological memories and specific antibodies through activation of T and B lymphocytes. Researchers have proved that β-glucan can modulate some important biochemical (serum hemoglobin, serum protein, and total hemocyte count) and immunological (lysozyme activity, phagocytic activity, oxidative burst activity, and phenoloxidase activity) properties providing more competent immune profile for treating fish and aquatic organisms. β-glucan-supplemented fish showed limited sensitivity of genes involved in acute inflammatory reactions. Findings have shown that β-glucan exerts a positive impact on fish and aquatic organisms’ immunity, enhancing their disease resistance by increasing functional and decreasing deleterious responses. This review focuses on the basic bump of β-glucan on fish and shellfish immunity and recent information on the uses of β-glucan in progressive aquaculture.